2008
DOI: 10.1097/jom.0b013e3181845f6c
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Function in Pesticide Workers

Abstract: Our data indicate that duration of work exposure in the pesticide processing industry may be associated with the development of acute and chronic respiratory symptoms and lung function changes. These effects appear to be aggravated by smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 14 publications
5
29
0
2
Order By: Relevance
“…In females, a significant relationship between duration of work and FEF25% was observed and duration of work was strongly associated with abnormalities in all lung function parameters in males [63].…”
Section: Chronic Bronchitismentioning
confidence: 95%
See 2 more Smart Citations
“…In females, a significant relationship between duration of work and FEF25% was observed and duration of work was strongly associated with abnormalities in all lung function parameters in males [63].…”
Section: Chronic Bronchitismentioning
confidence: 95%
“…These studies focused on the manufacture of pentachlorophenol [64] and chlorpyrifos [65], the packaging of liquid pesticides ( pyrethroids and carbamates) [62] and various other pesticides [63]. No association was observed among workers in 2,4,5-T production in one study [66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional study of workers in a bottling plant showed that in comparison with controls, pesticide processing workers had a significantly higher risk of developing respiratory symptoms, including chronic cough in females (OR = 1.29, 95% CI: 1.15–15.84), dyspnea grades 3 and 4 (OR = 1.11, 95% CI: 1.06–1.97 in females; OR = 2.35, 95% CI: 1.50–4.10 in males), throat irritation in males (OR = 1.36, 95% CI: 1.10–3.50), nasal catarrh (OR = 2.08, 95% CI: 1.12–3.40 in females; OR = 2.15, 95% CI: 1.15–4.10 in males), and nasal dryness (OR = 1.15, 95% CI: 1.05–2.91 in females; OR = 1.19, 95% CI: 1.10–3.15 in males) [44]. In addition, acute respiratory symptoms, such as cough, wheezing, chest tightness, dyspnea, throat irritation and dryness, nose secretion and dryness, were significantly increased across the work-shift among pesticide workers [44]. …”
Section: Pesticide-related Respiratory Symptoms and Diseasesmentioning
confidence: 99%
“…For example, in a patient reported as a case of occupational asthma related to chronic exposure to the fungicide captofol showed a substantial and persistent decrease in FEV 1 (forced expired volume in 1 s) [61]. A cross-sectional study among the pesticide-processing workers showed that there was significant reduction in FVC (forced vital capacity), FEV 1 and FEF 25%–75% (the forced expiratory flow between 25% and 75% of forced vital capacity) in comparison to controls [44]. Another cross-sectional study of 102 pesticide sprayers and 69 non-sprayers in state farms of Ethiopia showed that pesticide sprayers in the age group of 15–24 years had significantly reduced FEV 1 and FVC compared to controls [62].…”
Section: Pesticide-related Respiratory Symptoms and Diseasesmentioning
confidence: 99%